A high precision TDC design based on FPGA+ARM. Issue 7 (April 2020) - Zhang, MengDi; Wang, HuaChuang; Liu, Bo
Abstract: In this paper, a high precision time digital converter(TDC) is designed based on FPGA and ARM, It includes coarse module, delay chain module, look-up-table module, ringosc moduleand spi module in the FPGA chip. The ARM chip is used for reading the timestamp and printing through the serial port. The key technology of this design is using the CARRY4 block of Xilinx Aritex-7 series to construct a delay chain for finecount. The system clock is used as the coarse count. The timestamp is obtained by the combination of fine time and coarse time.In addition, the precison of TDC is improved by code density test. The experiment result shows that precision of TDC is 43.2ps.